2007
DOI: 10.1111/j.1440-1789.2006.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐bound crotonaldehyde accumulates in the spinal cord of superoxide dismutase‐1 mutation‐associated familial amyotrophic lateral sclerosis and its transgenic mouse model

Abstract: Growing evidence documents oxidative stress involvement in ALS. We previously demonstrated accumulation of a protein-bound form of the highly toxic lipid peroxidation product crotonaldehyde (CRA) in the spinal cord of sporadic ALS patients. In the present study, to the determine the role for CRA in the disease processes of superoxide dismutase-1 (SOD1) mutation-associated familial ALS (FALS), we performed immunohistochemical and semi-quantitative cell count analyses of protein-bound CRA (P-CRA) in the spinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Protein carbonylation measured immunologically revealed an almost exponential increase in these posttranslational modifications between 90 and 120 days in the SOD1 G93A mice . Lipid oxidation products are likewise increased in ALS mice spinal cords Perluigi et al 2005;Shibata et al 2007). Increased oxidative damage to DNA in spinal cord, cortex, and striatum of SOD1 G93A mice was reported as well (Aguirre et al 2005).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Protein carbonylation measured immunologically revealed an almost exponential increase in these posttranslational modifications between 90 and 120 days in the SOD1 G93A mice . Lipid oxidation products are likewise increased in ALS mice spinal cords Perluigi et al 2005;Shibata et al 2007). Increased oxidative damage to DNA in spinal cord, cortex, and striatum of SOD1 G93A mice was reported as well (Aguirre et al 2005).…”
Section: Discussionmentioning
confidence: 90%
“…Multiple studies demonstrated increased oxidative damage to proteins, lipids, and DNA in ALS post mortem tissues (Barber et al 2006;Ilieva et al 2007). Evidence for oxidative damage has been found in the spinal cord and in the motor cortex from sporadic ALS cases (Shaw et al 1995;Fitzmaurice et al 1996;Ferrante et al 1997a;Shibata et al 2007) and SOD1 familial ALS patients (Abe et al 1995(Abe et al , 1997Beal et al 1997). Markers for protein and lipid oxidation were detected in motor neurons, reactive astrocytes, and microglia or macrophages (Shibata et al 2001).…”
Section: Discussionmentioning
confidence: 93%
“…Immunohistochemical localization of P-HNE was verified by comparison with consecutive sections stained with H&E and immunostained with the antibodies to α-synuclein, ubiquitin, GFAP, and GLUT5, and it was also identified by the double-immunolabeled staining method as described previously [32]. Sections were incubated with one antibody, and immunoreaction was detected by the PIC method using DAB as the chromogen.…”
Section: Methodsmentioning
confidence: 99%
“…It can modify DNA by forming cyclic 1,N 2 -propanodeoxyguanosine adducts and can also induce micronuclei production and sister chromatid exchange (1,228). A potential role for crotonaldehydeprotein adducts in amyotrophic lateral sclerosis has been suggested (322). In mouse models of this disease, crotonaldehyde-immunoreactive neurons were identified and associated with the development of disease pathogenesis.…”
Section: Genetic and Related Cellular Effects Studiesmentioning
confidence: 97%